Mortality risk in cardiogenic shock: head to head comparision CardShock vs IABP score in a Mediterranean cohort: the Shock CAT study. (14th October 2021) - Garcia-Garcia, C; Lopez, T; Sanz, E; Sanchez-Salado, J C; Aboal, J; Tomas, C; Baneras, J; Sionis, A; Andrea, R; Perez-Rodriguez, M; Ariza, A; Pastor, P; et al.
Abstract: Background: Mortality in cardiogenic shock (CS) remains very high. Several risk scores have been purposed to early stratification. Purpose: The aim is to investigate in-hospital prognosis and mortality risk in CS patients comparing the prognostic accuracy of CardShock and IABP scores in a Mediterranean cohort. Method: Shock CAT study was a multicentre, prospective, observational study conducted between December 2018 and December 2019 in eight public University hospitals in Catalonia (Spain), including CS patients due to acute coronary syndrome (ACS) and other aetiologies. Data on clinical presentation, biomarkers, management, including mechanical assistance support were analyzed. Cardshock and IABP score have been compared to assess 90-days mortality risk in a Mediterranean cohort. Results: A total of 382 CS patients were included, mean age was 65.3 (SD 13.9) years and 75.1% were men. The most common cause of CS was ACS (61%, n=233); of them, 77.6% were STEMI, 9% developed mechanical complications and 19.4% primary ventricular fibrillation. STEMI patients were reperfused in 84.7% of cases, all with primary angioplasty. Main non-ACS aetiologies were severe acute heart failure, malignant arrhythmias and myocarditis. Mechanical assistance device was implanted in one third of patients (n=119), mainly intraaortic balloon pump (26.1%), ECMO in 7.8% and Impella in 4.5%. Average Cardshock score was 4.3 (SD 1.74) and mean IABP score was 2.2 (SD 1.61). In-hospital mortality was 33% (126 patients) and 90-days mortality was 37.3% (141 patients). Receiver-operating characteristic curves demonstrated that IABP shock score had superior prognostic power for predicting 90-days mortality when compared with Cardshock score (area under the curve 0.72 vs 0.66) respectively, p=0.042; Figure 1. Conclusions: Even though invasive management with STEMI reperfusion and mechanical assistance devices, cardiogenic shock in-hospital mortality remains 33% in a contemporary Mediterranean cohort. In this population, IABP shock score provided better 90-days mortality risk prediction than CardShock score FUNDunding Acknowledgement: Type of funding sources: None.